PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN TAHUN 2020 - Nasution, Anna Rizki (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
ABSTRACT The performance and quality of health services are very dependent on knowledge, skills and motivation. The results of interviews conducted with 10 employees of Padangsidimpuan City Hospital obtained information that there was no equal distribution of training for employees, 70% of the same employees participated in several trainings while 30% of other employees had never participated in training.The type and design of research is analytic survey with case control design. The population is all employees in the Padangsidimpuan City General Hospital, the sampling technique was purposive sampling with a sample size of 100 people. Data collection was carried out using a questionnaire. Data analysis is univariate, bivariate and multivariate analysis with multiple linear regression.The results showed the t test <0.05 or 4.488> 1.984 training affected the performance, motivation affected the performance with the t test <0.05 or 3.379> 1.984, the f test showed that the employee training affected the performance by 0.00 <0.05 with a calculated F value of 23.716> f table 3.09, motivation affects the performance of the f test value of 0.00 <0.05 with a calculated f value of 14.389> f table 3.09. and the test results of the determination of the value of the correlation / relationship (R) that is equal to 0.527 coefficient of determination (RSquare) of 0.278 means that 27.8% of training and motivation have an influence on employee work.Training should continue to be given continuously to each employee and provide incentives in accordance with the quality and workload at Padangsidimpuan City Hospital to improve the quality of services in hospitals. Keywords: Training, motivation, performance